Traumatic Aspects of Maoists’ Insurgency in Abhi Subedi’s Dreams of Mayadevi - Pokharel, Badri Prasad (KMC Research Journal, 2021)
This paper explores experience and perception of the traumatized people who have lost their near and dear ones in the Maoists’ insurgency. These people either depicted in the literary works or in newspapers have their testimony to share with others. Dreams of Mayadevi, a play written by Abhi Subedi has been taken as a testimony of the war victims who were badly crippled during the war. Mayadevi, the protagonist of this play who has lost her husband in Indian war and son, Siddhartha in the insurgency, and Salleri Sahinla who has lost all his family members are the victims and liable to share their painful testimony. To analyze this play, trauma theory has been analyzed. Theoretical parameter of some well-known theorists like Caruth, Lacrapa, Kirmayer etc. have been discussed to bring out the traumatic facts of the insurgency with the help of traumatized characters who represent all the victims of the war.